Psychoeducational support group to the resilience of caregivers of chronic kidney disease patients undergoing hemodialysis - Nuriyyatiningrum, Nadya Ariyani Hasanah; Siswadi, Ahmad Gimmy Prathama; Djunaidi, Achmad; Akorede, Quadri Mojeed (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
Making a resilient caregiver is important; in addition to lack of preparation, they are not adequately supported. Psychoeducational support groups can provide the necessary education about the conditions they are about to confront and create the sources of social support that will enable and fortify them when dealing with difficult conditions. This research aimed to understand the effect of a psychoeducational support group on caregivers' resilience of chronic kidney disease patients undergoing hemodialysis. Five subjects were used in this case study, which employed mixed methods using a concurrent embedded strategy that used primary quantitative data. The qualitative data analysis used thematic analysis, while the quantitative data analysis used Wilcox signed ranks test. Quantitative data analysis showed a p-value of .892, which led the researcher to conclude no differences between the pre and post resilience scores. Qualitative primary data analysis revealed that psychoeducational support group has a positive effect on caregivers’ resilience. Besides, this research discovered that a psychoeducational support group can significantly increase the perception of caring ability and ameliorate the difficulties in taking care of patients.